A methodology for numerically analysing the hepatic artery haemodynamics during B-TACE: a proof of concept. Issue 5 (4th April 2019) - Aramburu, Jorge; Antón, Raúl; Rivas, Alejandro; Ramos, Juan Carlos; Larraona, Gorka S.; Sangro, Bruno; Bilbao, José Ignacio
Abstract: Balloon-occluded transarterial chemoembolisation (B-TACE) is an intraarterial transcatheter treatment for liver cancer. In B-TACE, an artery-occluding microballoon catheter occludes an artery and promotes collateral circulation for drug delivery to tumours. This paper presents a methodology for analysing the haemodynamics during B-TACE, by combining zero-dimensional and three-dimensional modelling tools. As a proof of concept, we apply the methodology to a patient-specific hepatic artery geometry and analyse two catheter locations. Results show that the blood flow redistribution can be predicted in this proof-of-concept study, suggesting that this approach could potentially be used to optimise catheter location.